Private Guns:: The Social Identity of Security Contractors - Franke, Volker; Boemcken, Marc (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2009)
Abstract Accounts of human rights abuses and stories of shooting incidents have dominated the image of the private security industry in the media. Despite plenty of anecdotal evidence, to date there has been no empirical research analyzing whether there is a professional identity emerging among individuals who sign on with private security firms to assume roles traditionally reserved for the military. Using a survey of more than 200 American private security contractors with law enforcement backgrounds and operational experience in conflict regions, this research explores their social identities and examines the extent to which these identities shape their values, attitudes, and professional self-conceptions. It concludes with some preliminary recommendations for the future of outsourcing security functions to the private sector and the utility of using contractors in peace and stability operations.